Semiotics in Teh Botol Sosro’s Advertisement Ramadan Edition - Rendy Gunawan; Ervina CM Simatupang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze and examine the level of semiotics in the Ramadan edition of Tehbotol Sosro advertisements using Roland Barthes' semiotic theory. The data in this study are scenes that contain denotation and connotation meanings in the Ramadhan edition of Tehbotol Sosro advertisements that obtained from the video advertisement for the Ramadan edition of Tehbotol Sosro which was uploaded by the YouTube Channel account. This research method is descriptive qualitative. Research instrument is the researcher himself. Data collection was carried out by watching an advertisement for the Ramadan edition of Tehbotol Sosro, then taking screenshots of the scene containing denotative and connotative meanings. The results show that there are five denotative meanings, which is (50%) and connotative meanings, which is (50%) in Tehbotol Sosro advertisement Ramadan Edition. It can be seen that in the advertisement there is a direct meaning, namely denotation and an indirect meaning, namely connotation.